2021
DOI: 10.1186/s40163-021-00142-z
|View full text |Cite
|
Sign up to set email alerts
|

Six months in: pandemic crime trends in England and Wales

Abstract: Governments around the world have enforced strict guidelines on social interaction and mobility to control the spread of the COVID-19 virus. Evidence has begun to emerge which suggests that such dramatic changes in people’s routine activities have yielded similarly dramatic changes in criminal behavior. This study represents the first ‘look back’ on six months of the nationwide lockdown in England and Wales. Using open police-recorded crime trends, we provide a comparison between expected and observed crime ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 37 publications
8
57
0
Order By: Relevance
“…However, the lockdown may have reduced residents' fear of property crime since the neighbourhood may benefit from a safety in numbers effect described in environmental criminology literature (30) (i.e., residents' sense of safety is improved through the number of neighbours who are able to observe potential criminal behaviours). This view is also supported by a study that found a 60% reduction in property crimes in England and Wales during the first month of the UK national lockdown (31). The authors of the study attributed the decline in property crimes to having more "eyes on the street" as a result of the lockdown (i.e., neighbours act as surveillance which deters property crime).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the lockdown may have reduced residents' fear of property crime since the neighbourhood may benefit from a safety in numbers effect described in environmental criminology literature (30) (i.e., residents' sense of safety is improved through the number of neighbours who are able to observe potential criminal behaviours). This view is also supported by a study that found a 60% reduction in property crimes in England and Wales during the first month of the UK national lockdown (31). The authors of the study attributed the decline in property crimes to having more "eyes on the street" as a result of the lockdown (i.e., neighbours act as surveillance which deters property crime).…”
Section: Discussionmentioning
confidence: 81%
“…Meanwhile, certain components of social stressors related to physical decay (i.e., graffiti, vandalism, and trash on the streets) tend to persist and are unlikely to change over the relatively short study period. Unlike property crimes, there was no reduction in public order crimes (which include loitering and public intoxication) during the months of the web surveys ( 31 ). Thus, we are more confident that the change in association between social stressor and psychological distress reflects the lockdown condition rather than other influences such as “eyes on the street” or the reduction of public order crimes.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, what is clear from these data is that drug markets were significantly impacted by the COVID-19 lockdown. This contradicts the extant international and Australian city-or state-wide aggregate analyses (see, for instance, Langton et al, 2021) which has so far implied a significant stability and resilience of drug markets in the face of government mandated stay-at-home restrictions. We have witnessed in these data considerable local-level declines, specifically in the four main locations of Bowen Hills, Fortitude Valley, Roma Street and the Brisbane Casino, which were offset by an increase in detections elsewhere in the city.…”
Section: Discussionmentioning
confidence: 87%
“…COVID had clear effects on gender inequality (Czymara et al, 2020), education (Daniel, 2020), tourism (Sigala, 2020), and crime (Campedelli et al, 2020;Payne, 2020), among other social domains. While opportunities for many crime types decreased during COVID due to strict restrictions on social interaction (e.g., drug crime, street theft, residential burglary; Abrams, 2021;Langton et al, 2021), other crime types benefitted from it. Some clear examples of crimes that increased during COVID are domestic violence, since offenders and victims were confined together over long periods of time (Mohler et al, 2020;Piquero et al, 2020), and cybercrime and fraud, given the generalised increase in internet use for home working, online shopping, and leisure (Buil-Gil et al, 2020;Kemp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%